Image challenge: A sweet smelling rose or something fishier afoot? A man, an unusual rash and an unexpected diagnosis - Sinead McKiernan; Fiona McGill; Hugh McGann (Clinical Infection in Practice, 2023)
A 50-year-old male was seen in the infectious disease clinic with a 3 month history of multiple non-healing ulcers on his left arm. He found it difficult to flex this fifth and fourth digit but had no other associated symptoms. He was systemically well. Biopsies were taken for histological examination and microbiological culture. His markers of inflammation were normal, however, a routine HIV test was unexpectedly positive.